Evidences of the efficiency of public expenditure in the allocation of resources for fundamental education in the Brazilian states - Schuster, Herivélton Antônio; Zonatto, Vinicius (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
The objective this article is to evaluate the efficiency of public spending on education in the initial grades of education elementary, taking as a universe of analysis the set of 260 Brazilian municipalities, composed of the ten largest municipalities of each State, taking into account the most populous according to Database of the Brazilian Institute of Geography and Statistics (IBGE). The analysis was performed through the application of the Data Envelopment Analysis (DEA) technique, and the most adequate methodology is to measure the efficiency of the allocation of public resources to the various services provided. The results showed 13 municipalities with maximum efficiency in the allocation of resources, and 92.31% of these also reached the goal of the Development Index of Basic Education – IDEB in its entirety. It became evident that the municipalities with the highest cost per student enrolled and located in regions with greater economic development were less efficient.